The importance of lecturers' feedback in enhancing students' academic performance / Norshuhada Samsudin ... [et al.] - Samsudin, Norshuhada; Wan Mohd Rosly, Wan Nur Shaziayani; Syed Abdullah, Sharifah Sarimah; Ahmad Shukri, Fuziatul Norsyiha (Unit Penerbitan JSKM, 2025)
Lecturers’ feedback is an essential component of the learning process, significantly influencing students’ academic performance and overall development. Good feedback gives students precise direction on their development, assisting them in recognizing their strengths, addressing their weaknesses, and improving their comprehension of the course material. Additionally, it acts as a motivating tool, inspiring students to remain involved and actively participate in their education. Students can modify their study techniques as needed when they receive timely, constructive feedback that develops critical thinking, problem-solving abilities, and self-improvement. This paper explores the role of lecturers' feedback in higher education, emphasizing its importance in guiding students’ learning, enhancing comprehension, and fostering academic improvement. Various types of feedback, including written, verbal, formative, and summative feedback, are examined to highlight their impact on student performance. The study also discusses the benefits of constructive feedback, such as increased motivation, critical thinking, and self-reflection. However, challenges in delivering effective feedback, such as time constraints, student engagement, and clarity, are also acknowledged. Strategies for overcoming these challenges, including the use of digital tools and structured feedback methods, are proposed. By fostering a feedback rich learning environment, both lecturers and students can contribute to academic excellence and continuous improvement.